Relationships between accounting and intelligence: research paths - da Silva Momo, Fernanda (2021)
Objective: to identify the possible gaps and the development of knowledge in research on accounting and intelligence processes. Method: qualitative and quantitative study. A systematic literature review was carried out, analyzing 89 articles published in scientific journals, collected in July 2020. Originality/Relevance: accounting is increasingly taking part in decision-making processes and business management. Therefore, accounting science must appropriate strategic intelligence concepts since using information from outside the organization can assist in the more assertive measurement of accounting events and obtaining better information for decision making. Results: four main categories of research were observed in the articles analyzed. The use of Business Intelligence systems, improvement of accounting provisions, monitoring the environment to identify aspects relevant to the organizations’ financial life, and the automation of accounting processes through artificial intelligence and other technologies. Theoretical/Methodological contributions: this study offers a view on how accounting and intelligence branch out into different research categories. It was possible to identify research gaps and four categories in the development of knowledge on accounting and intelligence processes. Two of them refer to technology and process automation, one focused on managerial aspects of monitoring the environment, and one category is more technical focused on accounting calculation. The study’s methodological contribution lies in its form of systematization and illustration of the collection processes.